Cytotoxicity of quercetin and curcumin combination against HeLa cells line - Agitohutomo, Muhammad; Edityaningrum, Citra Ariani; Utari, Dina; Desvita, Widea Rossi; Aristiani, Windi; Nurani, Laela Hayu (Indonesian Journal of Pharmacology and Therapy, 2024)
Curcumin and quercetin combination are potential candidates for anticancer. Previous studies reported this combination active against several cancer cells including breast cancer, myeloid leukemia, and melanoma. However, the activity of this combination against cervical cancer has not been reported, yet. This study aimed to evaluate the cytotoxicity of the combination of curcumin and quercetin against HeLa and Vero cells. MTT assay was applied to evaluate cell growth inhibition. The inhibitory 50% concentration (IC50) of curcumin and quercetin on HeLa and Vero cells was determined and the selectivity index (SI) was then calculated. Combination index (CI) was calculated after evaluation of the cytotoxicity of the curcumin and quercetin combination at various concentration of 1 IC50, ½ IC50, and ¼ IC50. The IC50 of the curcumin against the HeLa and Vero cells were 26.57 ± 2.00 μM and 73.89 ± 12.93 μM with a SI of 2.78. Whereas the IC50 of the quercetin against the HeLa and Vero cells were 149.52 ± 21.09 μM and 1094.47 ± 15.68 μM with a SI of 7.32. The CI of combinations of curcumin and quercetin at concentrations of ¼ IC50 was 0.78 indicating a mild-moderate synergistic effect, whereas the combination at a concentration of 1 IC50 or ½ IC50, the CI value was >0.9 indicating an antagonistic effect.